The use of Nature-Based Solutions in the fight against Urban Floods: trends, actors and solutions adopted - Rodrigues, Maria Santiellas Costa; Quaresma, Cristiano Capellani; Pereira, Rodrigo Kuester; Ribeiro, Andreza Portella (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The growing and accelerated population concentration in urban areas, which was not accompanied by proper planning, resulted in several problems, which are even more profound in developing countries. With the elimination of natural vegetation cover, the waterproofing of the soil and other human actions that did not respect environmental dynamics, it is possible to observe increases in the number of occurrences and in the intensity of phenomena, such as floods and urban floods. Such problems affect especially the population layer in conditions of greater socio- environmental vulnerability, since they often occupy risk areas, such as the river plains. In order to combat this problem, alternative actions are being used to the detriment of conventional actions linked to gray infrastructure. In this sense, Nature-Based Solutions emerge as an alternative way to avoid and reduce the intrinsic impacts of urban floods in cities, as well as being implemented in different ways and in different locations. Therefore, this work sought to identify actions that are being used by several cities in the world with ways to combat urban floods through Nature- Based Solutions. Therefore, a Systematic Literature Review was carried out, with bibliometric analysis, in order to identify processes, actors and trends related to the theme. In this way, it is concluded that, despite the importance given to the subject having grown in the last 6 years, mainly due to the increase in scientific production and the amount of solutions implemented in several countries, such trends are concentrated, to a large extent, in European cities and observed by European actors.